Gamification based on a videogame that allows to develop tasks of high cognitive demand - Huiza Cribillero, Jasenia Fiorella (2019)
The gamification has begun its process of integration to the pedagogical method in Peru, although with scarce economic resources, the studies are based on free acquisition platforms in virtual media, one of them is studied in this research. 10 experimental activities were applied accompanied by the game Plants vs. Zombies, whose effectiveness was investigated in tasks of high mathematical cognitive demand, used a quantitative method, of a pre-experimental type, worked on a sample of 20 boys and girls in second grade of primary school (X(age) = 8.9 years ), the measurement was made from the adaptation of the Diagnostic Mathematics Assessment instrument, the results showed significant differences between the pretest and posttest measurements in the variable, which caused an influence on the level of achievement of the subjects, it was concluded that the game Plants vs. Zombies, accompanied by pedagogical strategies based on this videogame, caused more effectiveness in complex tasks (with and without information connections), as well as in the highest level of mathematical task requirements, this was evidenced in more than 50% of students.